Analisis Sumber Daya Teknologi Informasi dan Komunikasi untuk Sistem Pembelajaran Daring - Akhmad Bakhrun; Reynaldy Rizki Saputra; Muhammad Fauzan Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The research objective is to analyze information and communication technology resources in online learning systems. This research method is carried out starting from studying the literature related to the research topic then identifying the ICT resources used for online learning. The results showed that the information managed by the online learning system was 84.72% on average, the applications used were LMS Moodle (100%), Moodle runs on infrastructure with various specifications, and ICT human resources in higher education are on average as much as 54.55%. This study provides recommendations for universities wishing to develop an online learning system in their organization. Keywords: ICT Resources, PBM, Online Learning Systems, LMS, Higher Education